Meningkatkan Kognifitas Siswa Melalui Cooperatif Learning dengan Penerapan Model Pembelajaran Jigsaw - Fitriani; Ferina Yulianti; Ahsanur Rifqi; Tarsono; Hasbiyallah (Bidayatuna, 2023)
The learning model educators use in the learning process greatly supports achieving learning objectives, namely, getting maximum and optimal results. This study aimed to analyze the improvement of students' cognitive learning outcomes in PAI subjects by applying the Jigsaw-type learning model. This research method uses a quantitative type with a time-series experimental design, which examines groups from time to time through pre-test and post-test measurements or observations. The statistical test uses the paired sample t test. The results of the analysis of this study indicate that the Jigsaw Type learning model can improve students' cognitive learning outcomes in PAI subjects, as seen from the greater number of students who experienced an increase in learning outcomes after the application of the Jigsaw Type Cooperative Learning learning model, as much as 6.63%, the lowest 1.95%, and an average of 6.63%. Some factors that support improving students' cognitive learning outcomes in PAI subjects are: 1) cooperation; 2) collaboration; 3) awareness of responsibility; 4) students having the freedom to think creatively so that they are formed into active and independent students and can build cooperation and motivation between students in improving understanding of PAI lessons.